A theoretical study of grating effects on the performance of surface plasmon resonance sensing surface. (26th October 2021) - Nouri, Amin; Adelpour, Zahra; Sadeghi, Mojtaba
Abstract: The purpose of this paper is to conduct a theoretical analysis of the performance of a Surface Plasmon Resonance (SPR) sensing surface based on and the attenuated total reflection (ATR) phenomenon. Initially, the proposed structure comprises a prism, a thin gold layer, and an analyte. The effect of rectangular and triangular gratings on the SPR sensing surface's sensitivity is evaluated. The finite element method (FEM) simulation results indicate that the presence of gratings significantly increases the sensitivity of the structure to the point where the maximum sensitivity of 62.5 (deg/RIU) has been achieved for both gratings when the width and height are 5 nm and 15 nm, respectively.